2022
DOI: 10.1159/000526330
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of On-Site Evaluation of Cervical Cytology Smears Stained with Toluidine Blue to Reduce Unsatisfactory Results

Abstract: <b><i>Introduction:</i></b> Carcinoma of the uterine cervix is a major health problem faced by Indian women. Screening techniques like visual inspection with acetic acid, Lugol’s iodine, Papanicolaou smear, and human papillomavirus DNA testing have been suggested. Pap smear is a simple, safe, cost-effective, and reliable technique used for screening cervical lesions. Rapid on-site evaluation (ROSE) using the 1% aq. toluidine blue staining method has been less studied in cervical cytolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…[ 10 ] The NILM is the most common category reported in cervicovaginal Pap smears ranging from 68% to 96.31%. [ 5 - 7 , 9 ] In accordance with the results of earlier studies, we also found NILM in 86.87% of the cases (the most common interpretation category). However, it conflicts with the findings of Baamer et al ., who found that ASC-US (26.1%) was the most frequent interpretation category, and NILM was seen in only 8.9% of their cases.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…[ 10 ] The NILM is the most common category reported in cervicovaginal Pap smears ranging from 68% to 96.31%. [ 5 - 7 , 9 ] In accordance with the results of earlier studies, we also found NILM in 86.87% of the cases (the most common interpretation category). However, it conflicts with the findings of Baamer et al ., who found that ASC-US (26.1%) was the most frequent interpretation category, and NILM was seen in only 8.9% of their cases.…”
Section: Discussionsupporting
confidence: 91%
“…observed most common age group of screening patients was 31– 40 years, followed by 41–50 years. [ 7 ] Sharif YH and Baamer et al . observed that mean age of the study population was 31.55 ± 6.66 years (ranging from 21 to 60 years) and 45.12 ± 6.66 years (ranging from 21 to 75 years), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study had a significantly lower number of L1 cases with the implementation of ROSE. The utility of ROSE has been tested and implemented in various other studies and sites [[3], [19], [20]], and we highlight the same in lymph nodes for the first time in literature.…”
Section: Discussionmentioning
confidence: 97%
“…ROSE has been implemented in routine cytopathology practice for a long in various sites, i.e., breast, soft tissue, lymph nodes, thyroid, cutaneous sites, deep-seated lesions, and very recently in gynecological smears [3,[18][19][20]. It has been proved to be an adjunct to FNAC in reducing the unsatisfactory rates in ranges from 15-47% to 4-23% depending on the site of FNA [3].…”
Section: Discussionmentioning
confidence: 99%